(untitled) - Becker, Lucinda (New York, 2003)
The book will be a valuable asset throughout your degree course, supporting you as you aim to boost your degree profile and get good results, the troubleshooting guide at the start of each chapter will ensure that you stay on the right track. Once you have succeeded in your degree, it will assist you as you face the challenge of breaking into your chosen career
Keywords: Technology degree,Science; Management